Towards Sensor-Based Phenotyping of Physical Barriers of Grapes to Improve Resilience to Botrytis Bunch Rot - Herzog, Katja; Schwander, Florian; Kassemeyer, Hanns-Heinz; Bieler, Evi; Dürrenberger, Markus; Trapp, Oliver; Töpfer, Reinhard (Frontiers in Plant Science, 2022)
Botrytis bunch rot is the third of the economically most important fungal disease in viticulture (aside of powdery mildew and downy mildew). So far no active defense mechanisms and resistance loci against the necrotrophic pathogen are known. Since long, breeders are mostly selecting phenotypically for loose grape bunches as the most evident trait to decrease the infection risk of Botrytis bunch rot. The present study is focusing on plant phenomics of multiple traits by applying fast sensor technologies for measuring berry impedance (ZREL), berry texture and 3D bunch architecture. As reference, microscopic determined cuticle (MSCT) and infestation of grapes with Botrytis bunch rot was used. ZREL hereby is correlated to grape bunch density OIV204 (r=-0.60), the cuticle thickness of berries (r = 0.61), mean berry diameter (r = -0.63) as well as Botrytis bunch rot (r=-0.70). However, no correlation between ZREL and berry maturity or berry texture was observed. In comparison to the category of traditional varieties (mostly susceptible), elite breeding lines show an impressive increased ZREL value (+317) and a 1.0 µm thicker berry cuticle. QTLs on LG 2, 6, 11, 15 and 16 were identified for ZREL and berry texture explaining phenotypic variance between 3.0 % and 10.9 % providing the starting point for the development of molecular markers. Modelling ZREL and berry texture to predict Botrytis bunch rot susceptibility revealed McFadden R2 = 0.99. Taken together, the present study shows that in addition to a loose grape bunch architecture, the berry diameter, ZREL and berry texture values probably are additional parameter usable to identify and select Botrytis resilient wine grape varieties. Furthermore, grapevine breeding will benefit from these reliable methodologies permitting high-throughput screenings for additional resilience traits of physical barriers towards Botrytis bunch rot. The findings might also be applicable to table grapes and other fruit crops like tomato or blueberry.